2016
DOI: 10.22159/ajpcr.2017.v10i1.14655
|View full text |Cite
|
Sign up to set email alerts
|

A Clinicopathological Study of Allergic Rhinitis

Abstract: Objectives: Allergic rhinitis (AR) is on the rise in our society for various reasons. It is said that allergy might represent a primary or secondary factor in up to half the patients encountered in an otolaryngology practice. Thus, the management of AR constitutes a large proportion of the day-to-day practice. In addition to its primary effect, inhalant allergy of the upper respiratory tract might affect the development and clinical course of other disease states such as sinusitis, otitis media, and asthma due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…65.5% (95/145) when compared to males ie, 34.4 % (50/145). Bellamkonda M et al 15 in their study observed that female patients were slightly more than the male patients with a male to female ratio of 0.935:1 ie they had 31 females and 29 males in their study. Kammili J et al 12 observed allergic rhinitis more in males than in females, with 66.66% in males and 33.33% in females.…”
Section: Comparative Studies Related To Gender Distributionmentioning
confidence: 77%
See 4 more Smart Citations
“…65.5% (95/145) when compared to males ie, 34.4 % (50/145). Bellamkonda M et al 15 in their study observed that female patients were slightly more than the male patients with a male to female ratio of 0.935:1 ie they had 31 females and 29 males in their study. Kammili J et al 12 observed allergic rhinitis more in males than in females, with 66.66% in males and 33.33% in females.…”
Section: Comparative Studies Related To Gender Distributionmentioning
confidence: 77%
“…Wang W et al 14 reported the median age as 19.0 years. Bellamkonda M et al 15 in a similar study observed the youngest patient to be 16 years and the oldest as 45 years. The mean age of their study group was 27 years.…”
Section: Comparative Studies Related To Age Distributionmentioning
confidence: 80%
See 3 more Smart Citations